2003
DOI: 10.1111/1468-2389.00226
|View full text |Cite
|
Sign up to set email alerts
|

Selection in Teams: An Exploration of the Teamwork Knowledge, Skills, and Ability Test

Abstract: In 1994, Stevens and Campion introduced the Teamwork Knowledge, Skills, and Ability test (teamwork KSA test) for selecting employees for team-based organizations. Using experimental data from 57 ad hoc student teams (N 227), we examined this test's relationship with both the behavior of the assigned leader in a team and the behavior of the other team members, respectively. We found that the teamwork KSA test successfully predicted individual team member behavior as indexed by external raters (r .31) and peers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 55 publications
2
65
0
7
Order By: Relevance
“…Analogously, team structure also may be identified as salient in most team contexts. In terms of self-efficacy beliefs in team contexts, several researchers (Eby and Dobbins 1997;McClough and Rogelberg 2003;Haines and Taggar 2006;Staples and Webster 2007;Alavi and McCormick 2011) have focused on self-efficacy for teamwork, which refers to an '…individual's perceptions of his or her ability to perform generic teamwork behaviors' (Tasa et al 2007, p. 19). This construct is concerned with process aspects of teamwork, and has been found to relate to a range of teamwork behaviors, including cooperation (Eby and Dobbins 1997), conflict resolution, assuming leadership, and keeping on-task (Tasa et al 2007).…”
Section: Team Contextmentioning
confidence: 99%
“…Analogously, team structure also may be identified as salient in most team contexts. In terms of self-efficacy beliefs in team contexts, several researchers (Eby and Dobbins 1997;McClough and Rogelberg 2003;Haines and Taggar 2006;Staples and Webster 2007;Alavi and McCormick 2011) have focused on self-efficacy for teamwork, which refers to an '…individual's perceptions of his or her ability to perform generic teamwork behaviors' (Tasa et al 2007, p. 19). This construct is concerned with process aspects of teamwork, and has been found to relate to a range of teamwork behaviors, including cooperation (Eby and Dobbins 1997), conflict resolution, assuming leadership, and keeping on-task (Tasa et al 2007).…”
Section: Team Contextmentioning
confidence: 99%
“…Prior psychometric studies of the teamwork KSA test suggest studies can include the overall and also the two subscales. 26 The final data set included 245 responses.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…21,24,25 McClough and Rogelberg found that the teamwork-KSA test successfully predicted individual team member behavior such that higher scores on the teamwork-KSA test were associated to greater individual effectiveness within teams. 26 Their research provided evidence of the validity of the teamwork KSA measurement to assess teamwork competencies. The specific competencies that will be evaluated in this paper are self-management skills and interpersonal skills.…”
Section: What Is the Impact Of The Intervention (Collaborative Tool Amentioning
confidence: 99%
“…This instrument is a widely accepted quantitative assessment of team competencies 20 . The specific competencies that will be evaluated in this paper are self-management skills and interpersonal skills.…”
Section: What Is the Impact Of The Proposed Collaborative Tool And Thmentioning
confidence: 99%
“…McClough and Rogelberg 20 found that the teamwork-KSA test successfully predicted individual team member behavior such that higher scores on the teamwork-KSA test were associated to greater individual effectiveness within teams. Their research provided evidence of the validity of the teamwork KSA measurement to assess teamwork competencies.…”
Section: Dependent Variablesmentioning
confidence: 99%